DIGITAL FINANCIAL SERVICES: PERCEPTIONS, ONGOING USAGE AND SECURITY CONCERNS AMONG GEN Z - Ilyani Azer; Siti Aishah Mohamad; Musramaini Mustapha (Journal of Islamic, Social, Economics and Development, 2024)
Fin-tech used to describe emerging technology that aims to enhance and automate the provision of financial services. It uses specialized software and algorithms that are run on computers and, increasingly, smartphones to assist organizations, company owners, and individuals in better managing their financial operations, processes, and lives. The term "fin-tech" is a portmanteau of financial technology that includes digital financial services (DFS) and mobile banking which used to reshape the financial landscape. The globe is preferring cashless transactions and on the verge of becoming the norm, particularly after the pandemic's breakout. Accordingly, the financial sector employs digital services for their customer convenience. However, despite the benefits offered by DFS, there are drawbacks and security vulnerabilities have grown significantly, posing a significant problem for users. Gen Z is considered as digital natives as they are more info-tech literate and appears to be significant in the emerging market of fin-tech. Therefore, the study aims to identify Gen Z perceptions, intention to ongoing usage and security concerns toward DFS usage. An online survey was conducted on students at Universiti Teknologi MARA, Pahang Branch, Jengka Campus. The data from the survey was analyzed by using SPSS version 26. The result shows Gen-Z has positive perceptions towards DFS usage and they were aware of the security risks associated with DFS. The Gen-Z also has an intention for ongoing usage of DFS due to being influenced by positive perception and security concerns. This paper may be a useful source of information for the government and fin-tech businesses as they create the ecosystem for digital financial services along with future researchers that are interested in this field.